Evaluasi penerapan risk based internal audit pada PT. XYZ - Aisyah, Namirah; Fatima, Eliza (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to evaluate the implementation of Risk Based Internal Audit (RBIA) at PT ZYX, which conducted by SKAI to ensure the effectiveness of current internal control and provide recommendation required to increase the effectiveness of RBIA implementation. This study occurs in 2021 using study case qualitative approach through semi-structured interview. The result of analysis concludes that RBIA implementation by SKAI has not fully and comprehensively implemented. Therefore, several recommendations are provided to SKAI in order to improve the effectivity of RBIA implementation, such as to arrange standard audit, optimize of Audit Management System (AMS)’s utilization, conduct risk maturity assessment, and allocate audit internal resources.